Stevia: limiting cholesterol synthesis in Hep-G2 cells - Ilias, Amirul Nazhan; Hamzah, Hazilawati; Ismail, Intan Safinar; Ajat, Mokrish (Malaysian Society for Molecular Biology and Biotechnology, 2020)
As of today, no literature has been reported on the efficacy of stevia on lipid regulations conducted in vitro. Thus, the current study was focusing on the potential of Stevia rebaudiana bertoni as an anti-hypercholesterolemia substitute in limiting the de novo cholesterol synthesis in Hep-G2 cell line. The cytotoxicity and lipid internalization effects of stevia on Hep-G2 cells were assessed quantitatively and qualitatively in this study. As evaluated by MTT assay, commercialized stevia (0.5-20.0 mg/ml) and stevioside (1.0-10 µM) inhibited Hep-G2 cells viability in a dose-dependent manner for 24 hours. IC50 was detected at 8.68 mg/ml (commercialized stevia) and 10.91 µM (stevioside). From the assay, suitable concentrations were chosen to study the effect of stevia on cholesterol internalization in Hep-G2 cells supplemented with exogenous lipids. Cholesterol quantification assay revealed that high concentration commercialized stevia and stevioside promoted significant cholesterol internalized in Hep-G2 cells as compared to simvastatin. Finally, immunofluorescent microscopy assessment was done to qualitatively observe the formation of lipid droplets and low-density lipoprotein receptor in relation to total cholesterol extracted. The microphotographs of immunofluorescent microscopy were in parallel to results obtained from the cholesterol quantification assay which further revealed the effect of stevia as a potential antihypercholesterolemia agent.